Dhikr relaxation for middle-aged hypertensive patients to reduce insomnia - Nashori, Fuad; Khairunnisa, Nadea; Fitri, Khairunnisa; Puteri, Gita (INSPIRA: Indonesian Journal of Psychological Research, 2025)
Insomnia is a prevalent comorbidity among middle-aged individuals with hypertension. Dhikr relaxation, an Islamic spirituality-based intervention, has been proposed as a non-pharmacological approach to improve sleep quality. This study aimed to examine the effectiveness of dhikr relaxation therapy in reducing insomnia among middle-aged hypertensive patients. The study involved 18 participants aged 40–59 years diagnosed with stage 2 hypertension. Participants were randomly assigned to either an experimental group (n = 9) that received dhikr relaxation therapy or a control group (n = 9) that received no treatment. Insomnia was measured using the Athens Insomnia Scale (AIS) at the posttest and the two-week follow-up. Data were analyzed using paired t-tests and the Mann-Whitney U test, based on assumptions of normality and homogeneity. The results showed no statistically significant difference in insomnia scores between the experimental and control groups at both posttest and follow-up (p > 0.05). Additionally, there was no significant within-group change in insomnia scores over time. Dhikr relaxation therapy did not demonstrate effectiveness in reducing insomnia among middle-aged hypertensive patients. Potential confounding factors such as gender imbalance and participant background may have affected the results. Further studies with larger, more diverse samples and refined methodology are recommended.